Analysis of Village Fund Allocation Management in Overcoming Poverty Levels (Case Study in Bangun Rejo Village, Tanjung Morawa District in 2022) - Indri Andini; Sri Dewi Anggraini; Sri Maharani; Juliana Nasution (Journal of Indonesian Management, 2022)
The purpose of this study is to analyze the management of village funds in overcoming poverty levels in Bangun Rejo Village, Tanjung Morawa District in 2022. This research is qualitative in nature using secondary data obtained from the office of the Head of Bangun Rejo Village, Tanjung Morawa District. Village funds are funds sourced from APBN devoted to villages. This village fund is used to finance the implementation of village governance, implementation of village development, village community development, and also as village community empowerment. The purpose of village funds is to alleviate poverty. The results of the study show that Cash Transfer Assistance (BLT) can help the poor, but this program cannot increase the standard of living of the poor, let alone reduce the poverty rate. This is because the BLT program is still not assistance that leads to community empowerment, but is still limited as assistance that eases the burden on the poor to meet their daily food needs and payment of arrears.